Correlation and Examination of the Predominant Palatal Arch form within the Male and Female between North Indian and Negroid Population - Ishika Bhardwaj; Sally Lukose; M. Siddharth (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Palatal rugoscopy is the examination of the palatal rugae. The majority of people concur that a person’s rugae pattern remains constant throughout their lives. The rugae pattern can endure injury or burns better than most other anatomical structures because of their interior placement in the head. Because rugae patterns are believed to be unique, much like𿿿ngerprints, they re lso utilised for personal identi𿿿cation. Examining and correlating the dominant palatal arch form with the male and female groups in North Indian and Negroid populations was the aim of this study. The sample consists of 80 plaster casts, ages 18 to 25, split equally across two groups and genders. Method: After taking an impression of the maxillary arch, a plaster cast was made using alginate impression material. The rugae were recognised on the cast and described in accordance with Thomas and Kotze (1983) and Kapali et al. (1983) using a sharp graphite pencil and adequate illumination and magni𿿿cation esult: Class B (V-shaped palate) was the most common palatal arch form (16/40; 40.00%) in Negroid subjects, followed by Class C shape. In Indian subjects, Class C (U-shaped palate) was the most common palatal arch form (19/40; 47.50%), followed by Class A and Class B shapes.Conclusion: The rugae pattern is another method of distinguishing between North Indian and Negroid, based on the limitations of the current study.